Copeinca: a hostile takeover - Cueto, Diego C. (2017)
This article presents the dilemma faced by real investors with the emergence of a takeover bid on an existing company. The private benefits that accrue from control mean that defence mechanisms are deployed in the event of a takeover that is considered to be hostile. The article has been written with the sole intention of providing an educational case study for the teaching of Mergers and Acquisitions and Corporate Governance. The character Ricky Spanish is fictional and does not disguise the identity of any real investor. Local press articles and official documents such as company information prospectuses were examined during the preparation of the case study. The facts presented are accurate but the article is not intended to be a work of history. Theory-based analysis permits an approach to the problem of assessed value, which is contrasted with market value. Different scenarios and alternative viewpoints are presented to allow readers to draw their own conclusions. It is observed that the founding family, board members, company executives and press all fail to understand that the company is no longer owned exclusively by its founders. There is a lack of clarity concerning appropriate ways to deal with conflicts of interest between majority and minority shareholders. In markets characterized by decidedly concentrated ownership structures, it is very unlikely that hostile takeovers will occur. The case study identifies the principal benefits and risks faced by investors in a company from a medium income country that cross lists in developed markets.